ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF KOPI DENGAN ADANYA SERTIFIKASI COMMON CODE FOR THE COFFEE COMMUNITY (4C) DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Rina Astuti; Muhammad Irfan Affandi; Raden Hanung Ismono (Lampung University, 2021)
This research aims to analyze comparative advantage, competitive advantage, the impact of government policies on input output of certified coffee farming, and analyze the sensitivity of changes in input and outputprices to the comparative advantage and competitive advantage of coffee farming in Sumberejo Subdistrict Tanggamus District. The samples of 25 farmers were taken simply randomly from 133 coffee farmers who applied 4C coffee certification. Data were analyzed using PAM (Policy Analysis Matrix). The results showed that 4C certification coffee farming in Sumberejo Subdistrict of Tanggamus District had a competitive advantage with value of Private Cost Ratio of 0.53 and comparative advantage with of Domestic Cost Ratio of 0.38. Comparative advantage was sensitive to 20.31 percent decline in production volume and 40 percent decline in farm output price. Increase in input price due to revocation of subsidies reduced competitive and comparative advantages. Competitive and comparative advantages were not sensitive to an increase in input price.Key words: certified, coffee, comparative, competitive, PAM